1997
DOI: 10.1557/s109257830000171x
|View full text |Cite
|
Sign up to set email alerts
|

The role of gaseous species in group-III nitride growth

Abstract: A quasi-thermodynamic model accounting for kinetics of molecular nitrogen evaporation is applied to simulate the growth of binary and ternary group-III nitrides using atomic group-III elements and molecular ammonia as the sources. The values of the molecular nitrogen evaporation coefficients from the surface of GaN and AlN necessary for the simulation are extracted from experiments on free evaporation of the crystals in vacuum, while for InN only estimates are available. The growth process of AlN and InN is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In contrast, regimes II (W254) and III (W239) allow the main InN layer to be grown at maximal possible T S $ 470 C, when the In/N flux ratio is close to 1: 1 at given N flux and In droplets do not occur. This temperature agrees well with a lower boundary of theoretically estimated region of an onset of fast N escape from InN, resulting in an excess of In on the surface [3]. RHEED for both InN layers demonstrates (1Â1) streaky patterns corresponding to a 2D growth.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, regimes II (W254) and III (W239) allow the main InN layer to be grown at maximal possible T S $ 470 C, when the In/N flux ratio is close to 1: 1 at given N flux and In droplets do not occur. This temperature agrees well with a lower boundary of theoretically estimated region of an onset of fast N escape from InN, resulting in an excess of In on the surface [3]. RHEED for both InN layers demonstrates (1Â1) streaky patterns corresponding to a 2D growth.…”
Section: Resultssupporting
confidence: 86%
“…Indium nitride is considered as a promising material for optoelectronic devices, low-cost highefficiency solar cells, optical coatings, and various types of sensors [1]. However, due to a low dissociation temperature of InN (about 630 C [2]) and steep rising of nitrogen equilibrium vapor pressure with growth temperature (T S ) increase around 500 C [3], good quality InN epilayers are still not easily attainable. The lower growth temperatures and growth rates used in molecular beam epitaxy (MBE) could play a crucial role in growing the high quality InGaN alloys with high In content, necessary for achieving the green inter-band luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the occurrence of phase separation is determined by competition between the thermodynamic driving force and the compressive stress imposed by the lattice mismatch between the QWs and the barrier layers. The calculations of Karpov [14] showed that the elastic compressive stresses in In x Ga 1Àx N layers could shift the miscibility gap towards higher In concentrations, resulting in the suppression of phase separation. This is consistent with our experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, an In x Ga 1Àx N layer grown on a GaN layer will experience a compressive stress. The calculations of Karpov [14] showed that the elastic compressive stresses in In x Ga 1Àx N layers could shift the miscibility gap towards the higher In concentrations, leading to the suppression of phase separation in compositions where phase separation may be expected according to the calculations of Ho and Stringfellow [4]. Tabata et al [15] did not observe the Raman peak, which serves as the fingerprint of In-rich phase in Raman spectra obtained from pseudomorphic In x Ga 1Àx N layer ($3 nm) with 35% or 45% In.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism by which N is incorporated at the surface could not be identified. Theoretically, only few studies to describe GaN growth have been reported, which were either based on thermodynamic models [6] or Monte Carlo simulations [7]. These approaches are useful to model growth on a mesoscopic scale.…”
mentioning
confidence: 99%